Nitrogen and phosphorus dynamics in Nile tilapia farming in excavated rearing ponds (Research, Society and Development, 2020)
The purpose of this study was to determine the total nitrogen (TN) and total phosphorus (TP) balance during intensive tilapia farming in excavated ponds. To quantify TN and TP released into the environment, the supply water, effluents at the harvest time, fish composition, feed, and sediment were analysed. The mass balance between the amount of nutrients that is inserted through the feed, which is transformed into biomass by the fish and is retained in the sediment was calculated based on dry matter. The nutrient load arriving from the supply water was calculated as a function of the concentration of TN and TP. The TN and TP dynamics during the harvesting process in three different pond sizes identified that, on average, 2.37% of TN and 2.05% of TP inserted into the system during rearing is eliminated with 10.64% TN and 37.01% TP are retained in the sediment. The TN and TP input into the system occurs through the water supply, young fish, and the feed, the latter being responsible for about 92.87% TN and 96.05% TP. The feed composition indicates that the P level of the food is above the nutritional recommendations for the species. The amount of TP accumulated in the sediments indicates that there is a need for good management practices for water quality during the rearing and sediment management period before the beginning of a new production cycle.